Uma generalização do teorema de Ljusternik-Schnirelmann - Palmeira, Eduardo Silva (2005)
The purpose of this work is to present a generalized version of the classic Ljusternik-Schnirelmann theorem given by H. Steinlein [16] by using the con- cept of genus (c.f. [20]) of a Hausdor® space M with a mapping f : M ¡! M which generates a free Zp-action over M and to estimate the value of the genus of Lk;p, a special space used to construct an upper bound for the genus of (M; f).